Influence of Principalleadership and Teacher Teaching Performance on Learning Achievement of Students Class VIII of Al-Khairiyah Middle School (SMP) Surabaya - Rus man (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2018)
Abstract: This study is to determine the effect of principal leadership, teacher teaching performance on student achievement. The method used in this study was quantitative statistics. To get good and correct data, researcher used structured questionnaires and documentation. After the data was collected, it was analyzed using the product moment correlation formula, then continued by using multiple correlation formula, after that, it was proceeded bythe percent formula. To make easier to calculate and conclude, the researcher complements the pedestrian table, helper table and formulas of Fcalculation and F table. The findings of this study can be concluded: first, the principal leadership and the teacher performance could be said to have an influence / positive with a statistical value of 30.08, Second, from the result of statistical analysis using Two Paths with manual calculation it can be calculated as 12.22 and a significance of 5,93, 100% = 56.25%. This means that the contribution  of teacher performance on the learning achievement of the eighth grade students of junior high school (SMP) Al-Khairiyah Surabaya that if it is presented in percentage reaching 56.25%. Keywords: Leadership, Performance, Achievement